Konsep Produksi Dalam Al-Quran - Irshadi Fariz Suwitra (Universitas Muhammadiyah Sumatera Utara, 2021)
Production from an Islamic perspective is an activity carried out to add value to an item or create new uses and even new goods so that it is more useful in meeting needs by prioritizing the benefit side of something produced. The main purpose of production itself is to maximize all the resources that Allah has given to humans to be used to worship Allah and get the pleasure of Allah. In doing production according to the Islamic perspective, the most important thing is to be guided in accordance with the rules and teachings contained in the Qur'an. Production has three basic principles, namely trust, work, and professionalism. Islamic values in production are prioritizing the values of benefit. In Islamic economics, Production actors are strictly prohibited from producing goods or services that cause damage and loss to humans. In fact, not only for the benefit of humans but for the universe with all its contents. The word production may be difficult to find in the Qur'an, however, there are many verses that explain how to do production implicitly. As for the verses in the Qur'an that describe production, including Surah Al-Hadid verse 25, Surah An-Nabiya verse 80, Surah An Nahl verse 80-81, Surah Hud verse 37, Surah Hud verse 61, Surah Al-Qasas verse 73.